CORPORATE GOVERNANCE TERHADAP KINERJA PERUSAHAAN - Herman Darwis (University of Merdeka Malang, 2009)
The research aimed to provide empirical evidence that corporate governance implementation,managerial ownership, institutional ownership, board of executive, and independent executiveaffected corporate performance. Population of the research was companies listed at IndonesianStock Exchange (ISX) between 2006 2008; sampling method used was purposive sampling as well asmultiple regression analysis. The result showed the implementation of GCG affected corporate performance.This meant that if the listed companies at BEI and have been surveyed by IICG implement agood corporate governance, the performance would increase. The higher corporate governance wasmeasured by corporate governance index perception, the higher corporate obedience and result ina good corporate performance. Institutional ownership affected corporate performance. The greaterinstitutional share ownership, the better corporate performance. The result showed that controlfunction from the ownership did determine improving corporate performance. Managerial ownership,board of commissioner, and commissioner independent did not affect corporate.